Intravitreal injection versus sub-Tenon's infusion of triamcinolone acetonide for refractory diabetic macular edema: A randomized clinical trial - Bonini, M. A.; Jorge, R.; Barbosa, J. C.; Calucci, D.; Cardillo, J. A.; Costa, R. A. (Assoc Research Vision Ophthalmology Inc, 2005)
PURPOSE. To compare the effectiveness of posterior sub-Tenon's infusion (STi) and intravitreal injection (IVI) of triamcinolone acetonide (TA) for treatment of refractory diffuse diabetic macular edema.METHODS. Thirty-six phakic diabetic patients with refractory diffuse diabetic macular edema were prospectively enrolled. Patients randomly received either 40 mg STi or 4 mg IVI of TA. Comprehensive ophthalmic evaluation was performed at baseline and 1, 2, 4, 8 +/- 1, 12 +/- 2 and 24 +/- 2 weeks after treatment. Macular morphologic changes detected by optical coherence tomography and visual acuity, intraocular pressure, and lens status were evaluated.RESULTS. Twenty-eight patients (28 eyes) completed the 24-week study. Central macular thickness was significantly reduced in the IVI group when compared with the STi group at 2, 4, 8, 12, and 24 weeks after treatment (P < 0.01). Mean visual acuities (in logarithm of the minimum angle of resolution [logMAR]) at week-4, -8, and -12 follow-up examinations were significantly higher in the IVI group (0.74, 0.75, and 0.82, respectively) when compared with the STi group (0.88, 0.88, and 0.90, respectively; P < 0.01). A significant change from baseline in mean intraocular pressure (mm Hg) was seen at weeks 4 (+/- 3.21) and 8 (+/- 3.35) in STi the group (P < 0.01), and at week 8 (+/- 2.78) in the IVI group (P < 0.05). No patient had cataract progression during the study.CONCLUSIONS. Although the number of patients and length of follow-up in this preliminary study were limited, the changes in central macular thickness and visual acuity observed after treatment suggest that IVI TA may be more effective than STi for the management of refractory diffuse diabetic macular edema. Further studies are needed to confirm these preliminary findings.